Geoelectrical characterization and monitoring of slopes on a rainfall-triggered landslide simulator - Hojat, Azadeh; Arosio, Diego; Ivanov, Vladislav Ivov; Longoni, Laura; Papini, Monica; Scaioni, Marco; Tresoldi, Greta; Zanzi, Luigi (Journal of applied geophysics, 2019)
In this paper, we present the results of time-lapse electrical resistivity tomography (ERT) monitoring of rainfall-triggered shallow landslides reproduced on a laboratory-scale physical model. The main objective of our experiments was to monitor rainwater infiltration through landslide body in order to improve our understanding of the precursors of failure. Time-domain reflectometry (TDR) data were also acquired to obtain the volumetric water content. Knowing the porosity, water saturation was calculated from the volumetric water content and we could calibrate Archie's equation to calculate water saturation maps from inverted resistivity values. Time-lapse ERT images proved to be effective in monitoring the hydrogeological conditions of the slope as well as in detecting the development of fracture zones before collapse. We performed eight laboratory tests and the results show that the landslide body becomes unstable at zones where the water saturation exceeds 45%. It was also observed that instability could occur at the boundaries between areas with different water saturations. Our study shows that time-lapse ERT technique can be employed to monitor the hydrogeological conditions of landslide bodies and the monitoring strategy could be extended to field-scale applications in areas prone to the development of shallow landslides. •ERT was employed at lab scale to monitor rainfall-triggered shallow landslides.•Time-lapse ERT data could effectively monitor the internal conditions of the slope.•High saturations or saturation gradients can be precursors of potential instability.•Unstable zones were identified as high resistivity areas before slope failure.•Archie's law was calibrated to convert resistivity maps to water saturation maps.